Reconstructing the Concept of Khalwat Sahihah in the Digital Era: An Analysis of Scholars' Legal Perspectives - Musarrofa, Ita; Sa'adah, Mazro'atus (Institut Agama Islam Negeri Curup, 2023)
The digital era has opened up the possibility of long-distance sexual relations for married couples, commonly known as cybersex. This article aims to examine the relevance of cybersex between married couples with the debated concept of khalwat sahihah in the interpretations of various Islamic legal schools. Can long-distance sexual relations, such as cybersex, be categorized as khalwat sahihah with legal implications for dowry (mahar) and waiting period (iddah)? Then what are the legal consequences for dowry and iddah? Data on cybersex is collected from websites, and online articles about cybersex, as well as from research on cybersex that has been conducted. On the other hand, data regarding the debates among scholars from various Islamic legal schools (mazhab) about khalwat sahihah is gathered from books on comparative jurisprudence authored by Wahbah Zuhaily and Abdurrahman al-Jaziri. The data is then analyzed using content analysis and examined through the lens of the theory of maslahah. The research findings suggest that cybersex between husband and wife cannot be equated in terms of legal status with physical sexual intercourse, as cybersex entirely precludes physical contact. Cybersex is more relevant to the concept of khalwat sahihah, the law of which is being debated by school scholars. Cybersex is more relevant to the concept of khalwat á¹£aá¸¥Ä«á¸¥ah, which remains a debated issue among scholars from different Islamic legal schools (mazhab). According to the viewpoints of the Shafi'i and Maliki schools, cybersex between a husband and wife results in an obligation to pay only half of the dowry (mahar). In the Shafi'i school, divorce following the occurrence of cybersex does not obligate the wife to observe the waiting period (iddah). However, according to the Maliki school, the wife is still obligated to observe the waiting period (iddah). In the Hanafi and Hanbali schools, cybersex obligates the husband to pay half of the dowry (mahar) and requires the wife to observe a waiting period (iddah) similar to that after a divorce (iddah talak bain). To fulfill the sexual needs of LDR (Long Distance Relationship) couples, cybersex has maslahah value depending on the condition of each individual's sexual needs. Cybersex is only a means (wasÄ'il) that can change in realizing the goal (ahdÄf) of building a marital relationship that is sakinah, mawaddah and rahmah.